Corruption and Economic Growth in ASEAN-5 Countries - Firman Firman; Fathan Munim (Department of Development Economics, Universitas Sriwijaya, 2022)
The goal of economic development is economic growth nor foreign direct investment, but this increase must be supported by improving the quality of people, the population, and reducing the level of corruption. The purpose of this study is to determine the impact of corruption on economic growth and foreign direct investment. Using the variables of economic growth, foreign direct investment, corruption perception index, population, and human development index. The sample is ASEAN-5 countries, namely Indonesia, Malaysia, Singapore, Philippines, and Thailand from 2010-2020. The findings of our first model show that neither the corruption perception index nor the population index is significant, while the human development index has a positive relationship and has a significant effect on foreign direct investment in ASEAN-5. The findings of our second model are that the corruption perception index has a negative and significant effect on economic growth, while the human development index and foreign direct investment have no significant effect on economic growth in ASEAN-5.